PENGGUNAAN TELESKOP UNTUK RUKYAT Al-HILAL: ANALISIS PENDAPAT MUHAMMAD BAKHIT AL-MUṬĪ’I DENGAN IBNU HAJAR AL-ḤAITAMĪ - Desy Kristiane (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Determination of the beginning of the month on the lunar calendar is marked by the appearance of the new moon seen by the eye after sunset. To find out the appearance of the new moon it takes observation or rukyat. The scholars disagree with regard to the law on the use of assistive devices in rukyat al-hilāl, some do not allow it like Ibn Hajar al-Ḥaitamī and others allow it like Muhammad Bakhit al-Muṭī'i. The difference of opinion between al-Muṭṭ’i and Ibn Hajar al-Ḥaitamī because Muhammad Bakhῑt al-Muṭῑ’i is a scholar with Hanafi ideology, where the Hanafi school of thought is as a master of ra'yi, because he is proficient in using qiyas (analogy). While Ibn Hajar is a Shafi'i scholar whose style is a combination of ahlu ra'yi and ahlu hadith. Although their opinions differ, the stipulations of the law are the same, al-Muṭī'i allows but agrees with Ibn Hajar's reason